Grain productivity and quality of the facultative barley variety ‘Marusya’ when sowing in winter and spring - А. S. Popov; G. V. Ovsyannikova; А. А. Sukharev; А. А. Dontsova; G. M. Zelenskaya; О. S. Lesnykh (Зерновое хозяйство России)
The current study was carried out on ordinary blackearth (chernozem) in the southern part of the Rostov region in the FSBSI “ARC “Donskoy” (2017–2020 agricultural years). The purpose of the work was to identify the effect of autumn and spring sowing periods on grain productivity and quality of the facultative barley variety ‘Marusya’ according to various forecrops. There has been considered the dynamics of the productivity of the variety ‘Marusya’ depending on the sowing time when sown after maize for grain and sunflower. There has been established high adaptability of the variety ‘Marusya’ after nonfallow forecrops. It has formed a high productivity when sown in autumn at various times. There has been found out a positive reaction of the variety to sowing on September 10, 20 and 30, where the maximum productivity when sown after maize for grain was 6.76–6.91 t/ha. When sowing at later time, there was a slight decrease in productivity. When sown in spring, the highest protein percentage in grain was 11.0 and 11.6%. However, due to the highest productivity, the maximum protein yield was when sowing in autumn, up to 0.71 t/ha. The calculation of the economic efficiency of grain production showed that the highest profitability (214.1 and 214.4%) was obtained when the variety ‘Marusya’ was sown on September 10 and 20 after maize for grain. On average, over the years of study, the maximum conditional net income according to the forecrop, depending on the sowing time, was from 59658 to 84261 rubles/ha when sown in winter and from 48881 to 59170 rubles/ha in spring. The minimum profitability 62.1–75.2% was identified when sown in spring in 10 days after the soil was physically mature.